Diels-Alder reactivities of strained and unstrained cycloalkenes with normal and inverse-electron-demand dienes: activation barriers and distortion/interaction analysis. - Liu, F; Paton, R; Kim, S; Liang, Y; Houk, K (2013)
The Diels-Alder reactions of the cycloalkenes, cyclohexene through cyclopropene, with a series of dienes--1,3-dimethoxybutadiene, cyclopentadiene, 3,6-dimethyltetrazine, and 3,6-bis(trifluoromethyl)tetrazine--were studied with quantum mechanical calculations and compared with experimental values when available. The reactivities of cycloalkenes as dienophiles were found by a distortion/interaction analysis to be distortion controlled. The energies required for cycloalkenes to be distorted into the Diels-Alder transition states increase as the ring size of cycloalkenes increases from cyclopropene to cyclohexene, resulting in an increase in activation barriers. The reactivities of the dienes are controlled by both distortion and interaction energies. In normal Diels-Alder reactions with cycloalkenes, the electron-rich 1,3-dimethoxybutadiene exhibits stronger interaction energies than cyclopentadiene, but the high distortion energies required for 1,3-dimethoxybutadiene to achieve transition-state geometries overtake the favorable interaction, resulting in higher activation barriers. In inverse-electron-demand Diels-Alder reactions of 3,6-dimethyltetrazine and 3,6-bis(trifluoromethyl)tetrazine, the reactivities are mainly controlled by interaction energies.